PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PT. TRIMURI KARYA CIPTA - Waskito, Meindro; Kartini, Maelani Indah (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
The purpose of this study was to determine the influence of leadership and work motivation on work productivity of employees in the production division of PT. Trimuri Cipta Karya. The data collection technique uses a questionnaire with a Likert scale, with a population of 50 employees of the production department as the saturated sample used. Testing of the questionnaire instrument was carried out by testing the validity and reliability testing and then redistributing it to be processed and analyzed. The results of the research here with hypothesis testing (t test) produce t count = 3,476 > (larger) t table = 2,011 and a significant level of 0.001 < (smaller) 0.05 which means that Ho is rejected Ha is accepted then leadership (X1) has an influence and significant to the work productivity (Y) of employees in the production department at PT. Trimuri Cipta Karya. While the hypothesis test (t test)) between work motivation (X2) on work productivity (Y) resulted in a t count of 2.094 > (larger) t table = 2.011 with a significant level of 0.042 < (smaller) 0.05 which means that Ho rejected Ha is accepted then work motivation (X2) has a significant and the effect on work productivity (Y) of employees in the production division at PT. Trimuri Cipta Karya.